Fibonacci Numbers – Summation of Fibonacci Numbers with Odd and Even n

fibonacci-numbers

Compare the summation below:
$$\begin{align}
\smash[b]{\sum_{i=1}^n F_{2i-1}}&=F_1+F_3+F_5+\cdots+F_{2n-1}\\
&=1+2+5+\cdots+F_{2n-1}\\
&=F_{2n}\\
\end{align}
$$
with this one:
$$\begin{align}
\smash[b]{\sum_{i=1}^n F_{2i}}&=F_2+F_4+F_6+\cdots+F_{2n}\\
&=1+3+8+\cdots+F_{2n}\\
&=F_{2n+1}-1\\
\end{align}$$
When I first discovered these patterns I was amazed. Naively I had thought that an every-other-number sum of Fibonacci numbers would be the same pattern whether the parity of their indices was odd or even, but I was wrong! Why is the above true, where the summation of odd-indexed Fibonacci numbers is another Fibonacci number, but the even-indexed sum is a Fibonacci number minus 1?

Best Answer

Fibonacci numbers are defined by the recurrence relation,

$$F_n=F_{n-1}+F_{n-2},~~~F_1=F_2=1.$$

Rearranging, we have $F_{n-1}=F_n-F_{n-2}$. Letting $n=2k$,

$$F_{2k-1}=F_{2k}-F_{2(k-1)},$$

hence, the sum of odd-indexed Fibonacci numbers telescopes:

$$\sum_{k=2}^{m}F_{2k-1}=\sum_{k=2}^{m}(F_{2k}-F_{2(k-1)})=F_{2m}-F_{2}.$$

Since $F_1=F_2$,

$$\sum_{k=2}^{m}F_{2k-1}=F_{2m}-F_{2}\\ \implies F_1+\sum_{k=2}^{m}F_{2k-1}=F_{2m}\\ \implies \sum_{k=1}^{m}F_{2k-1}=F_{2m},$$

which is the formula the OP mentioned finding.

The derivation of the analogous formula for a sum of even-indexed Fibonacci numbers is highly similar. The key is the recurrence relation.